MODÉLISATION DE LA FONCTION DE LA DEMANDE DES DÉPENSES PUBLIQUES ALGÉRIENNE À L’AIDE DE MODÈLE ECM - Adouka, Lakhdar; Kchirid, El Mustapha; Benzekoura, Aonia; Bouguelli, Zohra (European Scientific Journal, ESJ, 2013)
The objective of this paper is to explain the growth of public spending by the approach of the demand for public goods in Algeian from 1970 to 2010, to test the veracity of Wagner’s law for the Algerian economy by an approach demand, to verify the positive effect between the share of public expenditure to GDP ratio and the following variables: the per capita income, population, urbanization, degree of economic openness, the effect of Baumol and macroeconomic stability.